Technology Education, Innovation, and Management
X, 318 p. 10 illus.
Keywords: Developing the interface between humans and technology involves the strategic question of how to connect innovation in teaching with the creation of value. Originating from an international conference on technology education, innovation and management, this book provides a focused overview of theoretical findings on this topic as well as starting points for practical work. It not only displays the existing level of international agreement, but also demonstrates a commitment to further development of technology education. For example, parallels between teaching innovation and the work situation in smaller firms point to a general trend toward linking value creation and education. The book presents theory and practice clearly arranged with diagrams, figures and tables.